The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jasms.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Picolinyl ester fragmentation mechanism studies with application to the identification of acylcarnitine acyl groups following transesterification

Abstract: Acyl picolinyl esters provide excellent data to identify the structures of acyl groups. However, the mechanisms for the formation of fragment ions from picolinyl esters are unsettled. Proposed structures for fragment ions have focused on long-chain groups and may not accommodate results from medium-and short-chain acyl groups. Using deuterium-labeled organic acids, we have investigated the mechanisms for the formation of fragment ions. Based on these studies, we propose a new mechanism that is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The method of Destaillats and Angers [18] was adapted for the transesterification of acylcarnitines [8]. Briefly, the residue containing acylcarnitines was reconstituted in 1.0 ml of anhydrous dichloromethane and reacted with a freshly prepared mixture of 100 l of 1.0 M potassium tert-butoxide in tetrahydrofuran and 200 l of 3-pyridylcarbinol.…”
Section: Transesterification Of Acylcarnitinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of Destaillats and Angers [18] was adapted for the transesterification of acylcarnitines [8]. Briefly, the residue containing acylcarnitines was reconstituted in 1.0 ml of anhydrous dichloromethane and reacted with a freshly prepared mixture of 100 l of 1.0 M potassium tert-butoxide in tetrahydrofuran and 200 l of 3-pyridylcarbinol.…”
Section: Transesterification Of Acylcarnitinesmentioning
confidence: 99%
“…We also have shown that the GC/MS spectra of the resulting acyl picolinyl esters can be used to deduce the chemical structure of corresponding acylcarnitines [8]. Meanwhile, the fragmentation mechanism of the 3-picolinyl 1570-0232/$ -see front matter © 2007 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fragments might be neutralized and thus not detected. The MS spectrum for DBA shows several signals that resulted from either cleaving or rearrangement in gas phase by mechanisms known as α-cleavage, β-cleavage, and Rearrangement migration shown [11][12][13][14] in schematic 3.…”
Section: Scheme 2 the Ei Removes An Electron From The Gas Phase Momentioning
confidence: 99%
“…The fragmentation mechanisms of all major peaks will comprehensively be analyzed (Yang, Minkler, Hoppel, & Tserng, 2006).…”
Section: Introductionmentioning
confidence: 99%